Transmedia Digital Design for Exhibition Spaces - Rodríguez Calatayud, Nuria; Heras Evangelio, David; Sanchis Gandia, Álvaro; Lleonart García, Melani (Eikón / Imago, 2019)
The authors propose to analyze and define some of the possibilities offered by nomadic digital technologies in the creation and dissemination of cultural content for exhibition spaces. Specifically, how the concept of interactivity has evolved in the last 5 years towards a new sample model or transmedia exposure. For this, they will focus the study on the analysis of three of their projects.